Assessing Concordance to an Intensified Upendo Ward Wilms Tumor Treatment Protocol in Tanzania: An Institutional Review (Tanzania Medical Journal, 2020)
Background: In Tanzania Wilms tumor (WT) ranks second among the most frequently diagnosed childhood cancer. Due to late presentation an intensified treatment protocol was established aiming for tumor reduction before surgery for achieving better surgical outcomes. We used two indicators for measuring the protocol concordance. First indicator was assessing the number of patients that received radiotherapy and second was number of patients treated with the high-risk regimen as per the protocol indications. Methodology: This was a cross sectional study. Data was collected using a retrospective chart review of all children with WT at Muhimbili National Hospital Pediatric Oncology Unit for a period between April 2016 to May 2017 who were treated using the intensified treatment protocol (combination of two WT protocols with neoadjuvant as per SIOP-PODC and adjuvant as per modified SIOP International). Analysis was conducted using excel sheet and SPSS v20. Results: A total of 74 children were eligible. The median age was 3 years ranging from 6 months to 17 years with small female predisposition of 57% (n=42). On clinical presentation all patients presented with history of abdominal swelling. In terms of clinical stage; 45% (n= 33) and 43% (n= 32) presented with stage 4 and 3 disease, respectively. Radiotherapy treatment was administered to 30% (n=22). As per protocol stage III and IV disease require radiotherapy thus only 34% of eligible candidates received radiotherapy. On histology report; 34% (n = 25) reports were never found and 66% (n=49) were available. High-risk cases were 27% (n = 20). We noted high-risk regimen was given to 12% (n=9) of study participants; thus only 45% of eligible candidates received high-risk regimen. All patient had intention to treat on admission with noted 19% (n = 14) default rate. Conclusion: Measuring concordance with guidelines allows for identification of best practices, which in turn inform on quality improvements. This snapshot identified opportunities for improvement in protocol uptake in our unit.Key words: Wilms Tumor, low income country, pediatric malignancy.